Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1097/mao.0b013e31821f473b
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation in Children With Cochlear Nerve Absence or Deficiency

Abstract: Cochlear nerve deficiency is not an uncommon cause for profound sensorineural hearing loss and presents a challenge in the decision-making process regarding whether to proceed with a cochlear implant. Children with a deficient but visible cochlear nerve on magnetic resonance image can expect to show some speech understanding after cochlear implantation; however, these children do not develop speech understanding to the level of implanted children with normal cochlear nerves. Children with an absent cochlear ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 25 publications
2
71
0
2
Order By: Relevance
“…An abnormal CVN has been reported in patients in whom the cochlear aperture size is normal or in patients with normal size IAC, or in patients with no associated cochleovestibular malformation [Glastonbury et al, 2002;Adunka et al, 2006Adunka et al, , 2007Buchman et al, 2006;Bradley et al, 2008;McClay et al, 2008;Carner et al, 2009;Warren et al, 2010;Kutz et al, 2011;Pagarkar et al, 2011;Colletti et al, 2014]. Our data highlight the association of normal cochleae, normal cochlear apertures, and normal caliber IAC with severe CVN abnormalities.…”
Section: Imaging Recommendationssupporting
confidence: 47%
See 2 more Smart Citations
“…An abnormal CVN has been reported in patients in whom the cochlear aperture size is normal or in patients with normal size IAC, or in patients with no associated cochleovestibular malformation [Glastonbury et al, 2002;Adunka et al, 2006Adunka et al, , 2007Buchman et al, 2006;Bradley et al, 2008;McClay et al, 2008;Carner et al, 2009;Warren et al, 2010;Kutz et al, 2011;Pagarkar et al, 2011;Colletti et al, 2014]. Our data highlight the association of normal cochleae, normal cochlear apertures, and normal caliber IAC with severe CVN abnormalities.…”
Section: Imaging Recommendationssupporting
confidence: 47%
“…Recent studies have reported an improvement in auditory skill development and sound awareness in children who had been diagnosed with CVN deficiency and received a CI [Casselman et al, 1997;Ito et al, 1999;Acker et al, 2001;Govaerts et al, 2003;Zanetti et al, 2006;Bradley et al, 2008;Oker et al, 2009;Kang et al, 2010;Warren et al, 2010;Buchman et al, 2011;Kutz et al, 2011;Young et al, 2012]. Clearly, some nerve fibers were available to transmit auditory signals to the brainstem [Casselman et al, 1997;Ozdoğmuş et al, 2004;Warren et al, 2010].…”
Section: Current Imaging Data Does Not Predict Auditorymentioning
confidence: 99%
See 1 more Smart Citation
“…Kutz et al [1] found that cochlear nerve hypoplasia or aplasia predicted poor outcome following cochlear implantation in children. A recent study in adult patients demonstrated a positive correlation between cochlear nerve size on magnetic resonance imaging (MRI) and post-operative auditory performance, as well as negative correlation between both the duration and degree of hearing loss and the size of the cochlear nerve [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) can directly assess these soft tissue structures responsible for hearing. Therefore, high-resolution brain (or internal auditory canal) MRI has been an important tool in investigating the etiology of deafness and in the selection process for cochlear implantation (CI) [Gleeson et al, 2003;Lapointe et al, 2006;Kutz et al, 2011]. Additionally, brain MRI allows physicians to detect abnormalities of the central nervous system (CNS) that may adversely affect neurological development as well as cognitive function [Bouhadiba et al, 2000;Hart et al, 2008].…”
mentioning
confidence: 99%